Kajian Kesiapan Komponen Wisata dalam Mendukung Pengembangan Wisata Pertanian di Desa Samiran, Boyolali - Heru Kurniawan; Wardatul Chamro'; Arya Bagus Firnanda; Dinda Putri; Trika Mayda (Universitas Kadiri, 2026)
Agriculture-based tourism is an important approach to supporting rural and agricultural development. To ensure its sustainability, this study aims to assess the readiness of tourism components in supporting the development of agrotourism, using a case study of Samiran Village, Selo District, Boyolali. The research employs a descriptive qualitative method, with data collection techniques including observation, in-depth interviews, and document analysis. Data analysis is conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that Samiran Village possesses all the components of tourism and is well prepared to support the development of agriculture-based tourism. This study recommends enhancing agricultural-based tourism, optimizing the sale of agricultural products to tourists, and developing educational tourism related to dairy cattle farming. Wisata berbasis pertanian merupakan upaya penting dalam pengembangkan pembangunan desa dan pertanian. Untuk menjaga keberlangsungan wisata tersebut, Penelitian ini bertujuan untuk menilai kesiapan komponen wisata dalam mendukung pengembangan wisata pertanian studi kasus di Desa Samiran, Kecamatan Selo, Kabupaten Boyolali. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan studi dokumentasi. Analisis data dilakukan secara deskriptif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Desa Samiran telah memiliki komponen wisata yang lengkap dan siap mendukung pengembangan wisata berbasis pertanian. Penelitian ini merekomendasikan peningkatan aktivitas wisata pertanian, optimalisasi penjualan produk pertanian kepada wisatawan, serta pengembangan wisata edukasi peternakan sapi perah.